THE IMPORTANCE OF CITY BIODIVERSITY INDEX (CBI) INDICATORS FOR MALAYSIA FUTURE BIODIVERSITY MANAGEMENT AT LOCAL LEVEL: A REVIEW - Norziana Ahli; Robiah Suratman (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Urban biodiversity conservation is typically practiced in densely populated areas or areas which experiencing rapid growth. The biodiversity population in urban areas has been severe affected because of urbanization. It is risky because uncontrolled urbanization will cause the extinction of urban species. The urban species richness require protection, and thus conservation will be successful if the government focuses on managing conservation properly. City Biodiversity Index (CBI) indicators will benefits in halting the loss of urban biodiversity and proving that it is a critical component in urban areas that require attention. The researcher highlights the critical components or indicators of CBI that lead to a better conservation of urban biodiversity in Malaysia.